HDL colesterol bajo como factor de riesgo cardiovascular en población rural, urbana y rural urbana migrante: Peru Migrant - Lazo Porras, Maria de los Angeles (2016)
Introduction: Whilst the relationship between lipids and cardiovascular mortality has been well studied and appears to be controversial, very little has been explored in the context of rural-to-urban migration in low-resource settings. Objective: Determine the profile and related factors for HDL-c patterns (isolated and nonisolated low HDL-c) in three population-based groups according to their migration status, and determine the effect of HDL-c patterns on the rates of cardiovascular outcomes (i.e. non-fatal stroke and non-fatal myocardial infarction) and mortality. Methods: Cross-sectional and 5-year longitudinal data from the PERU MIGRANT study, designed to assess the effect of migration on cardiovascular risk profiles and mortality in Peru. Two different analyses were performed: first, we estimated prevalence and associated factors with isolated and non-isolated low HDL-c at baseline. Second, using longitudinal information, relative risk ratios (RRR) of composite outcomes of mortality, non-fatal stroke and non-fatal myocardial infarction were calculated according to HDL-c levels at baseline. Results: Data from 988 participants, rural (n=201), rural-to-urban migrants (n=589), and urban (n=199) groups, was analysed. Low HDL-c was present in 56.5% (95%CI: 53.4%– 59.6%) without differences by study groups. Isolated low HDL-c was found in 36.5% (95%CI: 33.5–39.5%), with differences between study groups. In multivariable analysis, urban group (vs. rural), female gender, overweight and obesity were independently associated with isolated low HDL-c. Only female gender, overweight and obesity were associated with non-isolated low HDL-c. Longitudinal analyses showed that non-isolated low HDL-c increased the risk of negative cardiovascular outcomes (RRR=3.46; 95%CI: 1.23–9.74). Conclusions: Isolated low HDL-c was the most common dyslipidaemia in the study population and was more frequent in rural subjects. Non-isolated low HDL-c increased three- to fourfold the 5-year risk of cardiovascular outcomes.